Study of Using of Recycled Brick Waste (RBW) to produce Environmental Friendly Concrete: A Review (Journal of Engineering, 2021)
Several million tons of solid waste are produced each year as a result of construction and demolition activities around the world, and brick waste is one of the most widely wastes. Recently, there has been growing number in studies that conducted on using of recycling brick waste (RBW) to produce environmentally friendly concrete. The use of brick waste (BW) as potential partial cement or aggregate replacement materials is summarized in this review where the performance is discussed in the form of the mechanical strength and properties that related to durability of  concrete. It was found that, because the pozzolanic activity of clay brick powder, it can be utilized as substitute for cement in replacement level up to 10%. Whereas, for natural coarse aggregate, recycled aggregate can be used instead of it, but in limited replacement level. Concrete manufacturing from recycled aggregate can give adequate strength and can be suitable for the producing medium or low strength concrete. On the other side, the utilization of fine recycled brick waste as aggregate in the concrete manufacturing  provide development of the properties of concrete and it develops the durability of concrete in some cases when used with replacement level up to 10% by the weight of fine aggregate.